New derivatives of benzhydroxamic acid with nematocidal activity against Haemonchus contortus and Caenorhabditis elegans - Josef Krátký; Markéta Zajíčková; Aya C. Taki; Oliver Michel; Petra Matoušková; Ivan Vokřál; Karolína Štěrbová; Ondřej Vosála; Beate Lungerich; Thomas Kurz; Robin B. Gasser; Karel Harant; et al. (International Journal for Parasitology: Drugs and Drug Resistance)
Parasitic nematodes cause a wide range of diseases in animals, including humans. However, the efficacy of existing anthelmintic drugs, commonly used to treat these infections, is waning due to the increasing prevalence of drug resistance in nematode populations. This growing challenge underscores the urgent need to discover and develop novel nematocidal drugs that target new molecular pathways. In the present study, 13 novel derivatives of benzhydroxamic acid (OMKs) were designed and synthesized. Their anthelmintic activity was tested in the parasitic nematode Haemonchus contortus (barber's pole worm) and the free-living nematode Caenorhabditis elegans and potential toxicity assessed in mammalian models. Compound OMK211 showed the most promising results. It decreased viability and motility of larval and adult stages of both nematode species and of both drug-sensitive and drug-resistant strains of H. contortus at micromolar concentrations with the highest efficacy in H. contortus adult males (IC50 ∼ 1 μM). Moreover, OMK211 was not toxic in mammalians cells in vitro and in mice in vivo. Consequently, thermal proteome profiling analysis was used to infer the putative molecular target of OMK211 in H. contortus. The results revealed C2-domain containing protein A0A6F7Q0A8, encoded by gene HCON_00184,900, as an interacting partner of OMK211. Using advanced structural prediction and docking tools, this protein is considered an interesting putative molecular target of new nematocidal drugs as its orthologs are present in several nematodes but not in mammals. In conclusion, novel derivatives of benzhydroxamic acid represent a promising new class of potential anthelmintics, which deserve further testing.